Literature Review: Pendidikan kesehatan melalui diskusi kelompok dan curah pendapat terhadap pengetahuan dan sikap Pasangan Usia Subur (PUS) Akseptor KB AKDR - Nazirah Nazirah; Putri Santy; Nurlaili Ramli; Eva Purwita (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: There has been a decrease in the number of IUD family planning acceptors in the last three years, from 3.69% in 2016 to 3% in 2017 and 2018. One factor in the low use of IUD contraceptives is public perception. The way to change people's negative perceptions about the IUD is to provide health education.Objectives: To review several journals about effect of health education about iud (intrauterine) device uses group discussion and brainstorming on the level of knowledge and attitudes fertile age couples.Methods: The study is a literature review method based on the articles searched on Google Scholar and PubMed. The keywords used to find articles were using the keywords